VALUASI EKONOMI DAN STRATEGI PENGEMBANGAN WISATA MANGROVE DI DESA BALANG BARU KECAMATAN TAROWANG KABUPATEN JENEPONTO - Kaharuddin Kaharuddin; Muhammad Kasnir; Syahrul Djafar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
This study aims to determine the economic value of mangrove forests in Balang Baru Village and recommend strategies for developing mangrove forest tourism objects in Balang Baru Village, Kec. Tarowang Kab. Jeneponto. The results showed that the total economic value of the mangrove ecosystem in Balang Baru Village, Kec. Tarowang Kab. Jeneponto consists of direct benefit value, indirect benefit value, option value and existence value. Based on the results obtained, the focus of the strategy recommendations is then determined. The results of the analysis show that the strategy used is in diagram 1, which is to support an aggressive growth policy, where this position is a very profitable situation. The strategy used in the aggressive growth policy is optimizing the Balang Baru mangrove tourism attraction while maintaining its uniqueness and sustainability, providing guidance to tourism managers and coordinating with the government and other parties to support the development of mangrove tourism areas.